Next-Generation Dental Bone Implants − Sustainable 3D Nanostructures Derived from Animal By-Products: A Preliminary Study - Senthil, Rethinam; Kritika , Vajpayee (Biomedical Sciences and Clinical Medicine, 2025)
Objective The development of next-generation dental bone implants focuses on sustainable, bioactive materials derived from animal by pro-ducts, offering a cost-effective and eco-friendly alternative for bone regeneration. This study explores the fabrication of a 3D nano-structured dental implant (3D-DI) using fish bone collagen (FBC) and fibrin nanoparticles (FN), chosen for their excellent biocompatibility, bioactivity, and availability. Methods FBC and FN scaffolds were synthesized and incorporated into an implant framework. Fourier-transform infrared spectroscopy (FTIR) analysis confirmed the presence of bioactive functional groups. High-resolution scanning electron microscopy (HRSEM) characterized the porous microstructure (100–500 nm) as conducive to cell adhesion and proliferation. In-vitro cytotoxicity (MTT assay) and cell viability (live cell staining) were evaluated using MG63 osteoblast-like cells. Results The 3D-DI demonstrated significant bioactivity after 14 days in simulated body fluid (SBF), with a mineralization rate of 68% (p < 0.01). MG63 cell viability increased to 85% after 72 hours (p < 0.05) (ANOVA using Microsoft Excel Office 2013), indicating excellent biocompatibility. Mechanical testing showed compressive strength of 83.41 ± 0.56 MPa and tensile strength of 76.83 ± 0.81 MPa suitable for load-bearing dental and orthopedic applications (p < 0.05). Conclusions This study presents a novel approach for transforming animal waste into sustainable, bioactive dental bone implants, offering an eco-friendly alternative to conventional graft materials. Unlike previous reports that primarily focus on single-component or synthetic scaffolds, 3D-DI exhibits superior mechanical strength, enhanced mineralization, and excellent biocompatibility. These unique properties highlight its potential for load-bearing dental and orthopedic applications, addressing the current gap in development of cost-effective, high-performance biomaterials from bio-waste sources.